Benefits of Betel Leaves as a Medicine for Postpartum Perineal Wounds - Destiana, Ika; Nurhasanah, Nurhasanah; Triwahyuningsih, Ria Yulianti (Ann Publisher, 2024)
Indonesia is a country rich in natural materials for human health. One of them is red betel. This research was conducted to formulate red betel as a medicine for perineal wounds in mothers after childbirth. Making wound medicine by boiling. Boil 4-5 sheets or 9-11 grams (Piper Crocatum) that have been washed thoroughly, put 500 ml of water into a pot made of clay so as not to damage the substance content of red betel leaf (Piper Crocatum). Wait for it to boil for 15 minutes. Let the boiled water cool for 30 minutes, then strain the water and put the filtered result in the sterile bottle that has been provided. After that, respondents will use boiled water with red betel leaves (Piper Crocatum) after taking a shower in the morning and also in the afternoon. After finishing, the respondent will dry his female intimate organs with a towel until dry. Rinse the boiled water of red betel leaves (Piper Crocatum) once a scoop is given as much as 200 ml for one use.